Transforming Sundanese Local Values as an Architectural Identity of a Creative Hub in Bandung City - Al Iskandar, Muhammad Bhuana Yusuf; Herwindo, Rahadhian Prajudi (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2025)
Globalization has blurred local identity in architecture, resulting in public buildings that appear homogeneous and fail to reflect the cultural context of their surroundings. This phenomenon is evident in the city of Bandung, which despite its international recognition as a Creative City still faces challenges in optimizing creative hub buildings to meaningfully represent local identity and the dynamic nature of its creative industries. This gap between the city's creative image and its architectural expression leads to emotional disconnection between users and space, weakening the city’s narrative through architecture. This study aims to examine how creative hub architecture can represent local identity by transforming Sundanese cultural values into an adaptive and contextual design approach. The research employs a qualitative, descriptive, analytical, and interpretative method, focusing on the analysis of site, building mass, spatial layout, facade, and decorative elements. The study explores the potential of Sundanese cultural values in shaping architectural identity. The analysis is based on architectural identity theory, creative hub design classifications, and architectural metaphor theory that emphasizes symbolic representation, sense of place, and contextual connectivity. The findings reveal that integrating local values into design elements can create a strong, communicative, and contextually relevant architectural identity. This research highlights that identity representation is not solely achieved through formal expression but also through metaphorical approaches that embody intangible cultural values. The study contributes to the development of locality based creative hub design and supports the preservation of architectural identity in the face of globalization.